COVID-19: The new pandemic with many lessons and new challenges. Narrative Review - Valero-Cedeño, Nereida Josefina; Mina-Ortiz, Jhon Bryan; Veliz-Castro, Teresa Isabel; Merchán-Villafuerte, Karina Maricela; Perozo/Mena, Armindo José (Kasmera, 2020)
The new coronavirus (2019-nCoV, SARS-CoV-2 or COVID-19), which so far has affected more than 180 countries on almost every continent, was declared a pandemic by the World Health Organization. its global reach and to date, has exceeded one million infected cases, of which 5.54% have been fatal. The emergence of this disease has been explained by the presence of an unknown human coronavirus with increased virulence factors. The exponentially increasing number of cases in the world reflects in part the rapid transmission of COVID-19, which translates into a severe test for the health systems of the most affected countries. The challenges that this pandemic has represented, many have been based on the lessons learned from the SARS pandemic in 2003 and given the genomic similarity of this new strain of coronavirus, it has been designated as SARS-CoV-2. However, the like, there are many questions still to be answered, especially with regard to transmission mechanisms. Having detailed and accurate data will make it possible to understand and monitor the scope of this pandemic and strengthen prevention and response efforts, since the treatments are so far experimental and the vaccine may be available in the medium or long term.